Occult external iliac vein injury after anterior dislocation of the sacroiliac joint in adult patient - Yueju Liu; Juan Wang; Yingze Zhang (Acta Orthopaedica et Traumatologica Turcica, 2017)
Anterior dislocation of the sacroiliac joint, characterized by dislocation of the ilium anterior to the sacrum, is a subtype of complete posterior pelvic ring disruption. This injury occurs mostly in children. We present an adult patient with anterior dislocation of the sacroiliac joint. It was associated with numerous complications. To the best of our knowledge, it is only the second case reported in the literature. Keywords: Dislocation, Sacroiliac joint, Vascular injury, External iliac vein